A significant cathodic shift in the onset potential of photoelectrochemical water splitting for hematite nanostructures grown from Fe-Si alloys - Wang, Lei; Lee, Chong-Yong; Kirchgeorg, Robin; Hildebrand, Helga; Müller, Julian; Spiecker, Erdmann; Schmuki, Patrik (Materials Horizons, 2014)
Thermal oxidation of Fe to nanostructured hematite (wires, flakes) is currently widely investigated to produce efficient photoanodes for photoelectrochemical water splitting. The process carried out on pure iron, however, has the key drawback that not only hematite but a layered structure of Fe2O3-Fe3O4-FeO is formed where the thick suboxide layer underneath the Fe2O3 is highly detrimental to the photoresponse. In the present work, we show that suboxide formation can be largely suppressed if hematite nanowires/nanoflakes are thermally grown on Fe-Si alloys. For hematite structures grown on a Fe-Si alloy with 5 at% Si, a photocurrent onset potential as low as 0.6 V-RHE can be reached (under AM 1.5 illumination and 1 M KOH). We believe that the results represent a key finding towards the formation of optimized hematite nanostructures using a thermal oxidation method.

Enhanced Photoelectrochemical Water Splitting Efficiency of a Hematite-Ordered Sb:SnO2 Host-Guest System - Wang, Lei; Palacios-Padros, Anna; Kirchgeorg, Robin; Tighineanu, Alexei; Schmuki, Patrik (ChemSusChem, 2014)
Host–guest systems such as hematite/SnO2 have attracted a great deal of interest as photoanodes for photoelectrochemical water splitting. In the present work we form an ordered porous tin oxide layer formed by self-organizing anodization of Sn films on a FTO substrate. Subsequently the anodic tin oxide nanostructure is doped with antimony (ATO) by a simple impregnation and annealing treatment, and then decorated with hematite using anodic deposition. Photoelectrochemical water splitting experiments show that compared to conventional SnO2 nanostructures, using a Sb doped nanochannel SnO2 as a host leads to a drastic increase of the water splitting photocurrent response up to 1.5mA cm-2 at 1.6V (vs. RHE) in 1 M KOH under AM 1.5 (100mW cm-2) conditions compared to 0.04mA cm-2 for the non-Sb doped SnO2 scaffold.
EAM Import::2019-03-14

Excited state properties of anodic TiO2 nanotubes - Kahnt, Axel; Oelsner, Christian; Werner, Fabian; Guldi, Dirk Michael; Albu, Sergiu; Kirchgeorg, Robin; Lee, Kiyoung; Schmuki, Patrik (Applied Physics Letters, 2013)
Charge carriers, that is, holes as well as trapped and "free" electrons were investigated by means of time resolved spectroscopy in anodic TiO nanotubes that were heat treated at different temperatures. The lifetimes of the charge carrier were compared with those generated in reference layers of Solaronix Ti-Nanoxide D and Degussa P25 nanoparticles. Remarkably long lived "free" electrons were only noted in the TiO nanotubes. These findings have significance in view of any photoelectrochemical applications of TiO nanotubes. © 2013 2013 Author(s).

Formation of aligned nanoporous/nanotubular layers of vanadium oxy-nitrides - Yang, Yang; Kirchgeorg, Robin; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2014)
Self-organized vanadium oxy-fluoride nanotubular or nanoporous layers were grown by anodization of vanadium in a [BF4]- electrolyte. By a thermal conversion of this amorphous VOxFy precursor structure in ammonia gas, aligned vanadium oxy-nitride (VOxNy) nanoporous/nanotubular layers could be formed. We established conditions to reach conversion of precursor structures to a well crystallized VOxNy nanotube structure, without the formation of any secondary phases or the collapse of the ordered morphology. Such vanadium-nitride based structures have considerable potential in supercapacitor applications.
EAM Import::2019-03-14

Front side illuminated dye-sensitized solar cells using anodic TiO2 mesoporous layers grown on FTO-glass - Lee, Kiyoung; Kim, Dam-Hee; Berger, Stefan; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2012)
In the present work, we investigate the performance of anodic, self-organized TiO2 mesoporous structures (TMSs) in dye-sensitized solar cells (DSSCs) under front-side illumination conditions. In order to fabricate structures usable in a front-side (FS) configuration, TMSs were formed on FTO glass by a full anodic conversion of evaporated Ti films on the glass substrate in a glycerol/K2HPO4 electrolyte at 180 °C. The resulting mesoporous layers can be assembled to FS dye sensitized solar cells which show a thickness of only 3 extgreekmm and a remarkable efficiency of 4.34%. This is significantly higher than, for example, anodic TiO2 nanotubes of the same length even after efficiency enhancing TiCl4 treatments (3.01%). The best efficiency value for TMS-based DSSCs that we currently reached is for a 7 extgreekmm thick TMS layer, this is ≈6.82% which is highly promising for further improvements.
EAM Import::2019-03-14

Growth of ordered anodic SnO2 nanochannel layers and their use for H2 gas sensing - Palacios-Padros, A.; Altomare, Marco; Tighineanu, Alexei; Kirchgeorg, Robin; Shrestha, Nabeen Kumar; Diez-Perez, Ismael; Caballero-Briones, Felipe; Sanz, F.; Schmuki, Patrik (Journal of Materials Chemistry A, 2014)
In the current work, we present a new self-organizing anodization approach of metallic Sn layers to obtain vertically aligned tin oxide nanochannel structures. For this, we use a sulphide-containing electrolyte and a set of optimized anodizing parameters. The resulting high aspect ratio nanochannel morphologies can be converted into crystalline SnO2 by high temperature annealing and show highly promising H2 sensing properties. We show that these anodic layers can operate at relatively low temperatures ( 80 °C), detecting concentrations as low as 9 ppm, and with extremely fast response and recovery times. This excellent gas-sensing performance is ascribed to the advanced structure, characterized by a crack-free, straight and top-open nanochannel geometry.
EAM Import::2019-03-13

Hierarchical decoration of anodic TiO2 nanorods for enhanced photocatalytic degradation properties - Tsui, Lok-Kun; Nguyen, Nhat Truong; Wang, Lei; Kirchgeorg, Robin; Zangari, Giovanni; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work vertically aligned TiO2 nanorods were fabricated by anodization of Al/Ti dual layer structures. Anodization of Al leads to the formation of a porous alumina layer which is used as a template for the growth of TiO2 nanorods. We have studied the characteristics of these nanorods after annealing by high resolution TEM, showing a core–shell structure along the length of the nanorods formed from the expansion of the TiO2 nanorod into the alumina template during growth. Modification of the nanorods by spin coating of a solution of titanium isopropoxide (TIPO) in isopropanol yields enhanced photocatalytic activity up to 12 times due to the increase in surface area, light absorption volume, and the creation of a crystalline coating with an anatase-phase.
EAM Import::2019-03-13

Key factors for an improved lithium ion storage capacity of anodic TiO2 nanotubes - Kirchgeorg, Robin; Kallert, Max; Liu, Ning; Hahn, Robert; Killian, Manuela; Schmuki, Patrik (Electrochimica Acta, 2016)
In the present work we investigate key factors that influence the Li-storage capacity of anodically grown self-organized TiO2 nanotube layers. First, the influence of both tube length and top morphology are investigated regarding the rate performance of the nanotube layers. Then, factors such as the presence of initiation (grass) layers and the influence of the double walled morphology of conventional TiO2 nanotube layers are elaborated. At high C-rates a grass layer even shows a beneficial contribution, mainly by adding to the double layer capacitance. The presence of a double wall morphology and the associated carbon contamination lead to a lower intercalation ability. Two different approaches are taken to eliminate the inner carbon-rich layer: Cathodic polarization and tube formation in DMSO based electrolytes. This results in an enhancement of the areal capacity by 17% and 33% compared to unmodified tube layers for the two approaches.
EAM Import::2019-03-12

Molten o-H3PO4: A New Electrolyte for the Anodic Synthesis of Self-Organized Oxide Structures - WO3 Nanochannel Layers and Others - Altomare, Marco; Pfoch, Ole; Tighineanu, Alexei; Kirchgeorg, Robin; Lee, Kiyoung; Selli, Elena; Schmuki, Patrik (Journal of the American Chemical Society, 2015)
We introduce the use of pure molten ortho-phosphoric acid (o-H3PO4) as an electrolyte for self-organizing electrochemistry. This electrolyte allows for the formation of self-organized oxide architectures (one-dimensional nanotubes, nanochannels, nanopores) on metals such as tungsten that up to now were regarded as very difficult to grow self-ordered anodic oxide structures. In this work, we show particularly the fabrication of thick, vertically aligned tungsten oxide nanochannel layers, with pore diameter of ca. 10 nm and illustrate their potential use in some typical applications.
EAM Import::2019-03-12

NH3 treatment of TiO2 nanotubes: from N-doping to semimetallic conductivity - Al-Thabaiti, Shaeel A.; Hahn, Robert; Liu, Ning; Kirchgeorg, Robin; So, Seulgi; Schmuki, Patrik; Basahel, Sulaiman N.; Bawaked, Salem M. (Chemical Communications, 2014)
In the present work we show that a suitable high temperature ammonia treatment allows for the conversion of single-walled TiO2 nanotube arrays not only to a N-doped photoactive anatase material (which is already well established), but even further into fully functional titanium nitride (TiN) tubular structures that exhibit semimetallic conductivity.
EAM Import::2019-03-12

Role of Transparent Electrodes for High Efficiency TiO2 Nanotube Based Dye-Sensitized Solar Cells - Lee, Kiyoung; Kirchgeorg, Robin; Schmuki, Patrik (Journal of Physical Chemistry C, 2014)
In the present work, we investigate the performance of anodic TiO2 nanotube layers in dye-sensitized solar cells under front- and back-side illumination configurations. To fabricate transparent TiO2 nanotube electrodes, we evaporated 5 extgreekmm thick metallic Ti layers on FTO glass-then the metal layers are completely anodized to form aligned nanotube layers. We compare different types of FTO glass (conductivity and transparency) and use them for working electrodes as well as transparent platinized counter electrodes. The results show that for TiO2 nanotube electrodes the resulting light conversion efficiency in DSSCs is highly affected by the type of glass used (efficiency range-depending on configuration from 4.62% to 7.58%).
EAM Import::2019-03-13

Si-doped Fe2O3 nanotubular/nanoporous layers for enhanced photoelectrochemical water splitting - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2013)
The present work reports the enhancement of the photoelectrochemical water splitting performance of in-situ silicon (Si)-doped nanotubular/nanoporous (NT/NP) layers. These layers were grown by self-organizing anodization on Fe-Si alloys of various Si content. The incorporation of Si is found to retard the layer growth rates, leads to a more pronounced nanotubular morphology, and most importantly, an improved photoelectrochemical behavior. By increasing Si content from 1, 2 to 5 at.% in the iron oxide NT/NP photoanodes, the photocurrent onset potential shifts favorably to lower values. At 1.3 V vs. RHE, hematite layer with 5 at.% Si shows a 5-fold increase of the photocurrent, i.e. 0.5 mA cm- 2 in comparison to 0.1 mA cm- 2 for the undoped samples. The study also reveals that a suitable layer thickness is essential to achieve a beneficial effect of the Si doping.
EAM Import::2019-03-13

Tantalum Nitride Nanorod Arrays: Introducing Ni–Fe Layered Double Hydroxides as a Cocatalyst Strongly Stabilizing Photoanodes in Water Splitting - Wang, Lei; Dionigi, Fabio; Nguyen, Nhat Truong; Kirchgeorg, Robin; Gliech, Manuel; Grigorescu, Sabina Georgiana; Strasser, Peter; Schmuki, Patrik (Chemistry of Materials, 2015)
Ta3N5 nanostructures are widely explored as anodes for photoelectrochemical (PEC) water splitting. Although the material shows excellent semiconductive properties for this purpose, the key challenge is its severe photocorrosion when used in typical aqueous environments. In the present work we introduce a NiFe layered double hydroxide (LDH) cocatalyst that dramatically reduces photocorrosion effects. To fabricate the Ta3N5 electrode, we use through-template anodization of Ta and obtain oxide nanorod arrays that then are converted to Ta3N5 by high temperature nitridation. After modification with our cocatalyst system, we obtained solar photocurrents of 6.3 mA cm–2 at 1.23 VRHE in 1 M KOH, and an electrode maintains about 80% of the initial activity for extended irradiation times.
EAM Import::2019-03-12

Transparent Self-Ordered Niobium-Oxide Nanochannel Layers Formed on Conducting Glass by Total Anodization of Thin Metal Films in Glycerol/Phosphate Electrolyte - Barredo-Damas, Sergio; Lee, Kiyoung; Kirchgeorg, Robin; Sanchez-Tovar, Rita; Schmuki, Patrik (ECS Electrochemistry Letters, 2013)
In the present work, we show the feasibility to grow highly ordered anodic Nb2O5 nanochannel structures from a thin Nb-layer on conducting glass (fluorine doped tin oxide, FTO). This is achieved using a glycerol-phosphate electrolyte at 180◦C and a suitable anodization voltage that allows a rapid and complete conversion of the entire metallic layer into a transparent oxide layer of an extremely well defined directional nature with 20–30 nm wide open vertical channels. These layers can be used, either in the amorphous state or after thermal crystallization, for efficient reversible electrochromic switching devices.
EAM Import::2019-03-13

Transport properties of single TiO2 nanotubes - Stiller, Markus; Barzola-Quiquia, Jose; Lorite, Israel; Esquinazi, Pablo; Kirchgeorg, Robin; Albu, Sergiu; Schmuki, Patrik (Applied Physics Letters, 2013)
We investigated the electric transport properties of single TiO2 nanotubes separated from an anodic titania nanotube array. The temperature dependence of the resistance measured with the conventional four point method of all investigated samples show a Mott variable range hopping behavior. The results obtained with two contacts indicate the existence of a potential barrier between the Cr/Au contacts and samples surfaces, which influence is clearly observable at temperatures <150 K. Impedance spectroscopy in the frequency range of 40 Hz to 1 MHz carried out at room temperature indicates that the electronic transport of these polycrystalline tubes is dominated by the grain cores.
EAM Import::2019-03-13

Use of Anodic TiO2 Nanotube Layers as Mesoporous Scaffolds for Fabricating CH3NH3Pbl3 Perovskite-Based Solid-State Solar Cells - Salazar, Raul; Altomare, Marco; Lee, Kiyoung; Tripathy, Jyotsna; Kirchgeorg, Robin; Nguyen, Nhat Truong; Mokhtar, Mohamed; Alshehri, Abdelmohsen; Al-Thabaiti, Shaeel A.; Schmuki, Patrik (ChemElectroChem, 2015)
We optimize the deposition of CH3NH3PbI3 perovskite into mesoporous electrodes consisting of anodic TiO2 nanotube layers. By a simple spin-coating approach, complete filling of the tube scaffolds is obtained, which leads to interdigitated perovskite structures in conformal contact with the TiO2 tube counterparts. Such assemblies can be used as solid-state solar cells in a hole-transporting-material-free configuration, that is, the tube scaffold serves as electron collector and blocking layer, while the perovskite acts as visible-light absorber and hole-transporting material. We show that the complete filling of the tube scaffold with the perovskite is essential to improve the solar cell efficiency.
EAM Import::2019-03-12